RETENSI PROTEIN DAN RETENSI ENERGI IKAN CUPANG PLAKAT YANG MENGALAMI PEMUASAAN - Sukmaningrum S; Setyaningrum N; Pulungsari A.E (Journal Omni-Akuatika, 2014)
The aim of this study was to investigate the effect of periodic fasting on feed protein retention  and energy retention of betta fish (plakat) and the same or the best fasting regime with control on protein retention  and energy retention of betta fish (plakat). The method  used  in  this study  was  experiment  based  on  completely randomized design consisting of control K (feed daily) and 3 treatments ie: P1 (betta fish (plakat) was unfed for 1 days and 6 days refeeding), P2 (betta fish (plakat) was unfed for 3 days and 4 days refeeding), P3 (betta fish (plakat) was unfed for 5 days and 2 days refeeding). Six replicates were provided for the control and the treatments. The variables observed were protein retention  and energy retention. The experiments were conducted for 8 weeks. The result showed periodic fasting affect protein retention  and energy retention of betta  fish  (plakat).  Treatment  P1  (betta fish  (plakat)  was unfed for  1  days and  6  days refeeding each week) fasting regime the same with protein retention  and energy retention of betta fish (plakat). Key words: Betta fish (plakat), starvation, protein retention  and energy retention